Equivalence of the text in the translation (Eurasian Journal of Philology Science and Education, 2016)
Thearticlehereinconsidersawordin the literary text and in interlingual communication. It is noted, that the purpose of literary translation as a cross-language communication is to achieve equivalence between the original and final linguistic expressions, that translation complexity is due to the individual creative worldview of the writer, due to need to take into account the full semantic, functional and stylistic characteristics of the word with meanings augmentation, emotional and assessingverbal plan connotations. The author stresses, that the functional equivalence of texts is carried out with participation of semantic and communicative-pragmatic equivalence. Semantic equivalence can be complete and incomplete. Communicative and pragmatic equivalence is the types of translating such groups of emotionally colored words like swears (the largest group), addresses and figurative name unit. Peculiarity ofliterarytexttranslationisfelicitytotranslationinterpretationofaninitialtext; in that respect there is used the notions of linguo-ethnic communicative competence, linguistic-cultural communicative competence.
Keywords: semanticequivalency; interlingual communication; translation competence